Penatalaksanaan Perempuan Usia 48 Tahun Dengan Diabetes Melitus Tipe 2 Dan Prehipertensi Melalui Pendekatan Kedokteran Keluarga Di Wilayah Kerja Puskesmas Tanjung Sari Natar - Miranda, Alyzah Nabila; Angraini, Dian Isti (Medula, 2025)
Diabetes Mellitus is a metabolic disease characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action or both. Diabetes Mellitus is one of the degenerative diseases with a high prevalence and is increasing every year. There is a possibility of an increase in the number of people with Diabetes Mellitus in the future, so comprehensive management must be carried out which is expected to prevent complications and improve the quality of life of patients. The purpose of this case report is to apply Evidence Based Medicine-based services to patients by identifying risk factors, clinical problems, and patient management based on a patient problem-solving framework with a patient-centered, family-focused, and community-oriented approach. This study is a case report. Primary data were obtained through anamnesis, physical examination and home visits to assess the physical environment. Assessment based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. After the intervention, there was an increase in patient and family knowledge regarding the importance of health care checks, regular medication consumption, diet patterns and physical activity that are appropriate for people with Diabetes Mellitus. After holistic management with a family doctor approach, Mrs. N age 48 years with type 2 Diabetes Mellitus adjusted based on initial holistic diagnostics. The interventions carried out have increased patient and family knowledge about the importance of control to health workers, regular drug consumption, diet patterns and physical activity as indicated by improvements in the final holistic diagnostics.